Effects of different methods of strength training on indicators of muscle fatigue during and after strength training: A systematic review - Barahona Fuentes, Guillermo Daniel.; Huerta Ojeda, Álvaro Cristian.; Jerez Mayorga, Daniel. (Universidade Estadual Paulista, 2020)
Introduction: The development of strength has shown to be beneficial to sports performance and health. However, during strength training, they also produce alterations in muscle fatigue indicators, leading to a decrease in the ability to generate strength. Despite this, there is still not enough knowledge about the levels of muscle fatigue generated by different methods of strength training and how this information can be integrated into sports planning. Review and analyze the studies existing between January 2009 and January 2019 that have used indicators of muscle fatigue established in the search terms during and after strength training as measurement variables. Evidence acquisition: The study corresponds to a systematic review of previously published studies, following the PRISMA model. Articles published between 2009 and 2019 that measured muscle fatigue indicators during and after strength training were evaluated. The electronic search was conducted through Web of Science, Scopus, Sport Discus, PubMed, and Medline. We included all articles that used a strength protocol and also measured indicators of muscle fatigue and its possible effect on physical performance. Evidence synthesis: A total of 39 articles were found, which were stratified according to the protocol used: (i) plyometric training, (ii) Bodypump® training, (iii) occlusion training, (iv) variable resistance training, (v) conventional strength training, (vi) eccentric strength training, (vii) rest times in strength training and (viii) concurrent training. Conclusion: At the end of the systematic review, it was shown that the different training methodologies for strength development generate increases in muscle fatigue indicators, and the increase generated in the different muscle fatigue indicators depends both on the methodology used and on the type of population, sex, level of training and type of sport. The most-reported indicators are [La], HR and RPE, DOM, MR variation, and ammonium.
Keywords: Strength training.; Muscle fatigue indicators.; Sports performance.